Living with multimorbidity? The lived experience of multiple chronic conditions in later life. (November 2020) - Porter, Tom; Ong, Bie Nio; Sanders, Tom
Multimorbidity is defined biomedically as the co-existence of two or more long-term conditions in an individual. Globally, the number of people living with multiple conditions is increasing, posing stark challenges both to the clinical management of patients and the organisation of health systems. Qualitative literature has begun to address how concurrency affects the self-management of chronic conditions, and the concept of illness prioritisation predominates. In this article, we adopt a phenomenological lens to show how older people with multiple conditions experience illness. This UK study was qualitative and longitudinal in design. Sampling was purposive and drew upon an existing cohort study. In total, 15 older people living with multiple conditions took part in 27 in-depth interviews. The practical stages of analysis were guided by Constructivist Grounded Theory. We argue that the concept of multimorbidity as biomedically imagined has limited relevance to lived experience, while concurrency may also be erroneous. In response, we outline a lived experience of multiple chronic conditions in later life, which highlights differences between clinical and lay assumptions and makes the latter visible.